Relationship between knowledge, attitudes and practices in the prevention of the ergonomic risks of nursing professionals at the Good Hope Clinic, Lima, 2016 - Tipantuña Malte, Paulina (2019)
Objective: To determine the relationship between knowledge, attitudes and practices in the prevention ofergonomic risks of nursing professionals at the Good Hope Clinic. Materials and Methods: Cross-sectionalcorrelational design. The sample was non-probabilistic and by convenience, conformed by 130 professionalsof Nursing. The instruments used for the data collection were of own elaboration counting with a validity of1 through V of Aiken and a reliability of 0,890 with Alpha of Cronbach. Results: The chi-square test showedthat there is a relationship between knowledge and practices (p = 0.025) in the prevention of ergonomic risks.However, there is no relationship between knowledge and attitudes (p = 0.076) and between attitudes andpractices (p = 0.133). Conclusions: A relationship was found between knowledge and practices towards theprevention of ergonomic risks.